Implementasi Pembelajaran IPA Sekolah Dasar Berbasis Kearifan Lokal di Kabupaten Sragen - Saputri, Alifia Nugrahaning; Desstya, Anatri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This research highlights the value of local wisdom embedded in the Javanese community, especially in the Sragen area. The aim of this study is to determine the influence and improvement of the implementation of local wisdom-based science learning models on students' creativity and learning outcomes. This research uses a qualitative approach with the method used being descriptive. With this qualitative approach, the researcher will examine in-depth the implementation of local wisdom-based science learning. The type of research used in this study is a case study. In this case, to obtain a comprehensive picture of the implementation of local wisdom-based science learning in elementary schools in Sragen Regency, the focus of the study is on the teacher and 18 fifth-grade students of SD Negeri Teguhan. The results of this study prove that the local wisdom-based science learning model can improve students' creativity and learning outcomes.